Clinical Characteristics of Rhabdomyolysis in Children : Single Center Experience - Yesul Park; Ji Yeon Song; Su Young Kim; Seong Heon Kim (Korean Society of Pediatric Nephrology, 2018)
Purpose Rhabdomyolysis is a metabolic disorder in which the content of damaged muscle cells is released into plasma. Its manifestations include asymptomatic, myalgia, gross hematuria, and complications of acute kidney injury. Because of limited data on rhabdomyolysis in children, we performed this study to determine clinical characteristics of rhabdomyolysis in children. Methods We retrospectively reviewed the records of patients with rhabdomyolysis who were treated at the Pusan National University Children's hospital from January 2011 to July 2016. The diagnostic criteria were serum myoglobin level of ≥80 ng/mL, exclusive of acute myocardial injury, cardiac arrest, and brain damage. Results Forty-five patients were enrolled; mean age, 116±68 months. Of these, 35 were boys and 10 were girls. Twenty-six patients experienced myalgia and 12 patients showed gross hematuria. Among these, seven patients initially had both myalgia and gross hematuria. The most common causes of rhabdomyolysis were infection, physical exertion, prolonged seizures, metabolic abnormalities, and drug addiction. Acute kidney injury (AKI) was the most common complication, followed by disseminated intravascular coagulation. Thirty-seven patients improved with sufficient fluid supply but two patients underwent hemodialysis due to deterioration of kidney function. Gross hematuria, positive occult blood test, and positive urine protein were more common in patients with AKI than in those without AKI. Conclusions In children, infection was the most common cause of rhabdomyolysis. Most patients recovered by sufficient fluid therapy. However, in severe cases, especially in patients with underlying kidney disease, hemodialysis may be necessary in the present study.